2020
DOI: 10.3390/ijtpp5030022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Underlying RANS Turbulence Models in Zonal Detached Eddy Simulation: Application to a Compressor Rotor

Abstract: The present study focuses on the impact of the underlying RANS turbulence model in the Zonal Detached Eddy Simulation (ZDES) method when used for secondary flow prediction. This is carried out in light of three issues commonly investigated for hybrid RANS/LES methods (detection and protection of attached boundary layer, emergence, and growth of resolved turbulent fluctuations and accurate prediction of separation front due to progressive adverse pressure gradient). The studied configuration is the first rotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This is particularly advantageous when boundary-layer separations occur, since the method has been designed to switch to LES from the separation point, in order to deal with the limitations of RANS regarding separated flows. Although extended to other turbulence models [15], the ZDES formulation used for the present study is the original one and most mature, validated by Riéra on the first rotor of CREATE, associated to the Spalart-Allmaras model (SA model). The second mode of ZDES is used to ensure the RANS treatment of the attached boundary layers, where it is generally welladapted.…”
Section: Numerical Studymentioning
confidence: 99%
“…This is particularly advantageous when boundary-layer separations occur, since the method has been designed to switch to LES from the separation point, in order to deal with the limitations of RANS regarding separated flows. Although extended to other turbulence models [15], the ZDES formulation used for the present study is the original one and most mature, validated by Riéra on the first rotor of CREATE, associated to the Spalart-Allmaras model (SA model). The second mode of ZDES is used to ensure the RANS treatment of the attached boundary layers, where it is generally welladapted.…”
Section: Numerical Studymentioning
confidence: 99%
“…Providing that the software and its associated methodology are accurately validated, high-fidelity methods are thus expected to help engineers to improve aerodynamic designs of turbomachines, leading to fuel and emissions reductions of future aero-engines. Several high-fidelity methods have been developed, that can be sorted into two categories, according to the wall treatment: either the flow is resolved up to the wall, as performed in direct numerical simulation and in wall-resolved large-eddy simulation (Dupuy et al , 2020; Priebe et al , 2020; Scillitoe et al , 2017), or a model is used to predict the flow close to the wall, as in wall-modeled large eddy simulation (Odier et al , 2021; Perez-Arroyo et al , 2021) and in the different approaches based on the detached eddy simulation (DES) (Liu et al , 2019; Marty and Uribe, 2020), for which a RANS model is used close to the wall. The first category allows reaching precisely wall bounded flows on a limited domain such as a small amount of blades.…”
Section: Introductionmentioning
confidence: 99%
“…Computational models of compressor cascades have been used to investigate how different turbulence models predict corner separation flows and turbulence anisotropy [8,9]. In a study simulating a rotor in a high-pressure compressor, it was shown that the choice of turbulence model significantly influences the prediction of corner separation [10]. A simulation of the flow through an impeller at 80% speed was performed to compare the performance of the experimental stage with the performance predicted by Spalart-Allmaras, SST, and RS turbulence models.…”
Section: Introductionmentioning
confidence: 99%